Reading Skill Tested In English State Examination Paper For Junior High School Year 2009th - 2013th - Lestari, Sri; , Prof. Dr. Endang Fauziati, M. Hum; , Aryati Prasetyarini, M. Pd (2015)
This research aims at analyzing the reading skill tested in English state examination paper for Junior High School year 2009th - 2013th. It is conducted to know the aspects question of reading comprehension tested in English state examination paper from 2009th - 2013th at Junior High School. The researcher gets the data of this research from documents. The techniques of collecting data is documentation in reading comprehension tested 2009th - 2013th of English state examination paper. The result of this analysis shows that: 1). The aspects of reading skill tested in question about the ideas of the passage: 2009th (18%), 2010th(32%), 2011th(34%), 2012th (30%), and 2013th (36%); 2). The aspects of reading skill tested in directly answered question: 2009th (46%), 2010th (42%), 2011th (38%), 2012th (38%), and 2013th (40%); 3). The aspects of reading skill tested in indirectly answered question: 2009th (6%), 2010th (6%), 2011th (4%), 2012th (2%), and 2013th (0%); 4). The aspects of reading skill tested in vocabulary question: 2009th (16%), 2010th (8%), 2011th (6%), 2012th (10%), and 2013th (8%); 4). The aspects of reading skill tested in overall review question: 2009th (14%), 2010th (12%), 2011th (18%), 2012th (20%), and 2013th (16%). The conclusion of this research are the dominant aspect question of reading skill in the years 2009th - 2013th is directly answered question, which the specific presentage in the year of 2009th 46%, 2010th: 42%, 2011th: 38% ,2012th: 38%, and 2013th: 40%.